A conceptual model of business drawing insights from Indian philosophical thought. (2018) - Rath, Mrunmayee; Srivastava, Jaya
New paradigms of doing business are evolving as the world is facing a host of problems such as ecological imbalance, destruction of environment, corruption in business organisations and global financial crisis. It has been observed that business has often failed in the areas of ethics, social responsibility and sustainability. Commencing from the 'financial profit' motive, business has come a long way; but has still failed to meaningfully address various social and ethical concerns. Study of the emerging trend of business advocates the need for a holistic solution driven by spirituality. The Indian philosophy is the oldest living tradition with an ethical doctrine derived from its metaphysics giving it the capacity to provide solution to various problems of life. In this paper an attempt has been made to propose 'a conceptual model for business based on the insights gleaned from the rich Indian philosophical thoughts.